The Influence of Lifestyle and Price Perception on Coffee Purchase Decisions Among Generation Z in Medan - Ihdina Gustina (Outline Publisher, 2026)
Purpose: This study investigated the influence of lifestyle and price perception on the coffee purchase decisions of Generation Z consumers in Medan City. Methods: The researchers employed a quantitative approach with a causal-associative design. The study focused on consumers who purchased coffee at thirty-five local coffee shops. Data collection involved distributing structured questionnaires to one hundred and fifty respondents selected through purposive sampling. The researchers analyzed the collected data using multiple linear regression. Results: The analysis revealed that both lifestyle and price perception positively and significantly impacted purchase decisions. Specifically, price perception demonstrated a stronger influence compared to lifestyle. The statistical results indicated that lifestyle and price perception simultaneously accounted for forty-three point five percent of the variance in purchase decisions. Conclusions: The findings concluded that while Generation Z consumers strongly pursued modern social lifestyles, their limited financial capacity made rational economic calculations a more dominant factor in choosing a coffee shop. Originality/value: Therefore, coffee shop businesses must balance aesthetic social spaces with psychological pricing strategies to remain competitive.